Bone Regeneration in Artificial Jaw Cleft by Use of Carbonated Hydroxyapatite Particles and Mesenchymal Stem Cells Derived from Iliac Bone. (26th March 2012) - Yoshioka, Motoko; Tanimoto, Kotaro; Tanne, Yuki; Sumi, Keisuke; Awada, Tetsuya; Oki, Nanae; Sugiyama, Masaru; Kato, Yukio; Tanne, Kazuo
Abstract : Objectives of the Study . Cleft lip and palate (CLP) is a prevalent congenital anomaly in the orofacial region. Autogenous iliac bone grafting has been frequently employed for the closure of bone defects at the jaw cleft site. Since the related surgical procedures are quite invasive for patients, it is of great importance to develop a new less invasive technique. The aim of this study was to examine bone regeneration with mesenchyme stem cells (MSCs) for the treatment of bone defect in artificially created jaw cleft in dogs. Materials and Methods . A bone defect was prepared bilaterally in the upper incisor regions of beagle dogs. MSCs derived from iliac bone marrow were cultured and transplanted with carbonated hydroxyapatite (CAP) particles into the bone defect area. The bone regeneration was evaluated by standardized occlusal X-ray examination and histological observation. Results . Six months after the transplantation, perfect closure of the jaw cleft was achieved on the experimental side. The X-ray and histological examination revealed that the regenerated bone on the experimental side was almost equivalent to the original bone adjoining the jaw cleft. Conclusion . It was suggested that the application of MSCs with CAP particles can become a new treatment modality for bone regeneration for CLP patients.